Decreasing the ability of HCT116 cells to escape from therapy induced senescence by increasing the duration of doxorubicin treatment - N. A. Persiyantseva; S. Yu. Vikhrova; M. S. Korotkova; D. B. Kazansky; V. V. Tatarsky; M. A. Zamkova (Успехи молекулярной онкологии)
Contacts: Maria Anatolievna Zamkova zamkovam@gmail.com Introduction. Due to the toxicity of high doses of chemotherapy, low concentrations used in cancer treatment leads to the development of senescence phenotype in tumor cells, characterized by a block in the cell cycle progression and the absence of division; changes in the transcriptional and metabolic profile of cells. A negative consequence of this stage is acquisition of individual cells the ability to escape from senescence and return to re-proliferation.Aim. To estimate the effect of the duration of drug treatment of HCT116 tumor cells on their ability to escape from therapy induced senescence.Materials and methods. The senescence phenotype was confirmed by the analysis of β-galactosidase activity; cell cycle analysis; estimation of protein levels by western blotting. Colonies were stained with crystal violet dye.Results. In our study, we showed that the duration of HCT116 cells incubation with low-dose doxorubicin affects their ability to return to re-proliferation – increasing the treatment time using same drug dose reduces the process of colony formation. The duration of doxorubicin treatment does not affect the formation of the senescence phenotype, which was confirmed by analyzing different markers of this stage (changes in β-galactosidase activity, cell cycle analysis, assessment of p21 and γH2AX protein levels). However, there is a delay in the development of cellular response to DNA damage caused by doxorubicin in cells exposed to prolong treatment protocol (increase in β-galactosidase activity, formation of polyploid cells).Conclusion. The duration of doxorubicin treatment of HCT116 cancer cells affects long-term consequences, reducing the ability of senescent cells to escape this stage when the incubation time with the drug is extended.